2006
DOI: 10.1093/ps/85.5.837
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Genetic Correlation Estimates for Performance and Carcass and Body Composition Traits in a Male Broiler Line

Abstract: The current research was conducted to estimate the heritability coefficients and the genetic correlations for performance and carcass and body composition traits in a single sire broiler line. The performance traits analyzed were BW at 38 d, ultrasound records of pectoral muscle depth, feed intake, feed conversion ratio, and BW at 42 d. The carcass traits analyzed were eviscerated BW, breast weight, and leg weight, and the body composition traits analyzed were abdominal fat content, heart weight, gizzard weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
94
7
31

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(170 citation statements)
references
References 17 publications
37
94
7
31
Order By: Relevance
“…Heritabilities for C P , B w , L w , AF w traits were estimated at moderate-high levels to be 0.42, 0.36, 0.34 and 0.40, respectively. Heritability estimates of eviscerated and carcass weights of poultry were reported as generally moderate and high by various researchers (Toelle et al, 1991;Gaya et al, 2006). Heritability estimates of C P , B P , L P , AF P traits were estimated as low-moderate, viz.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Heritabilities for C P , B w , L w , AF w traits were estimated at moderate-high levels to be 0.42, 0.36, 0.34 and 0.40, respectively. Heritability estimates of eviscerated and carcass weights of poultry were reported as generally moderate and high by various researchers (Toelle et al, 1991;Gaya et al, 2006). Heritability estimates of C P , B P , L P , AF P traits were estimated as low-moderate, viz.…”
mentioning
confidence: 99%
“…Toelle et al (1991) determined a high genetic correlation between eviscerated weight and breast weight, and similarly, Vali et al (2005) reported high genetic correlations between eviscerated weight and leg weight. Additionally, there is a rather high genetic correlation between abdominal fat and carcass yield in poultry (Gaya et al, 2006).…”
mentioning
confidence: 99%
“…No entanto, em frangos, os resultados encontrados por Wang et al (1991), Argentão et al (2002) e Gaya et al (2006) indicam forte associação entre o peso vivo e o peso de carcaça, variando de 0,85 a 0,97.…”
Section: Resultsunclassified
“…For slaughter weight in chicken, heritability coefficients between 0.24 and 0.37 have been reported (Le Bihan-Duval et al, 1999;Gaya et al, 2006;Vayego et al, 2008). These values indicate that the individual pre-selection for any of these traits could lead to a good response in the selection, since they have additive genetic components in their expression.…”
Section: ----------------------------------------------------Eigenvecmentioning
confidence: 99%
“…US presents moderate to high heritability, as Gaya et al (2006) reported heritability coefficients of 0.28 and 0.29 for the depth of breast muscle measured by ultrasonography. For slaughter weight in chicken, heritability coefficients between 0.24 and 0.37 have been reported (Le Bihan-Duval et al, 1999;Gaya et al, 2006;Vayego et al, 2008).…”
Section: ----------------------------------------------------Eigenvecmentioning
confidence: 99%